Предмет:
МатематикаАвтор:
анонимВычислим значение выражения 2^(3/2) * 6^(-1/2)/9^(-1/6) * 3^(5/6).
2^(3/2) * 6^(-1/2)/9^(-1/6) * 3^(5/6) = 2^(3/2) * (2 * 3)^(-1/2)/(3 * 2)^(-1/6) * 3^(5/6) = 2^(3/2) * 2^(-1/2) * 3^(-1/2)/(3^(-1/6) * 2^(-1/6)) * 3^(5/6) = 2^(3/2 - 1/2 + 1/6) * 3^(-1/2 + 1/6 + 5/6) = 2^(9/6 - 3/6 + 1/6) * 3^(-3/6 + 1/6 + 5/6) = 2^(6/6 + 1/6) * 3^(-2/6 + 5/6) = 2^(7/6) * 3^(3/6).
В итоге получили, 2^(3/2) * 6^(-1/2)/9^(-1/6) * 3^(5/6) = 2^(7/6) * 3^(3/6).
Автор:
makenzie2onmДобавить свой ответ
Предмет:
ЛитератураАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть